STRATEGI TELEVISI LOKAL, MEMBENTUK OPINI PEMILIH PEMULA DENGAN CERDAS - Pamungkas, Hery (Interaksi: Jurnal Ilmu Komunikasi, 2015)
Abstract:The problem of this research starting from lack of beginner voter participation in using their voting rights, as well as the still lack of government support in the socialization of democratic education for voters. The purpose of this study to determine how effective the approach of local TV (TVKU Semarang) in cooperation with the Commission (KPU of Semarang) through the general elections program OSIS (Pemilos) in improving the level of awareness and understanding of political actualization of the students as voters. This research uses descriptive quantitative research methods. The population of this study were 100 high school students in the city of Semarang were aged 17-21 years and has attended educational programs democracy "Pemilos" student council president election race SMA/ SMK / MA State/ Private in 2012. While the number of respondents who researched many as 30 those students who had attended pemilos taken by accidental sampling technique (sampling incidentally). Results of this study states that most of the respondents agreed that the synergy between local television as a medium in this case by the KPU as election organizers and quite a significant correlate positively affect participation in the event turn out elections are held. And the most important thing is expected to increase voter turn out in the city of Semarang well in the election of DPR, DPD and DPRD as well as the election of President and Vice-President or elections simultaneously th 2015.